PERCEPÇÃO DE DEFICIENTES VISUAIS SOBRE SEXUALIDADE: PERCEPTION OF THE VISUALLY IMPAIRED ON SEXUALITY - Burtett, Caroline (2011)
This study examines the perception of the visually impaired on sexuality. It is a descriptive, qualitative research. Participants were seven subjects of both genres. The instrument used for data collection was an interview. Data analysis was based on the technique of discourse analysis. The results indicate that there is a deficiency in sex education for the visually impaired, for the information coming from family, school or other groups is not enough. In practice, they develop the sense of touch as the main tool for their sexual discoveries. Although their easy speech about sexuality, they feel the need of accessible / tactile material for better learning. Visually impaired people are still victims of prejudice. This is the greatest impediment to a full experience of sexuality. It is necessary to provide a further reflection of the real possibilities that the blind have to be complete in their loving, emotional, and sexual life.